Comparative exploration of the carotid body in domestic animals: morphology, physiology, histology, and pathology - Ecaterina, Semzenisi; Hodor, Dragos; Sall, Ibrahima Mamadou; Toma, Corina; Tăbăran, Alexandru-Flaviu (Frontiers in Veterinary Science, 2024)
The aim of the study was to present a review of the literature and research on the carotid body (CB) over the past years and update the latest findings. The purpose of this article is to present a general overview and comparative analysis of CB between species, from the microanatomy to the pathology of CB. This study gives information about the embryological development and physiological aspects of anatomical findings and their differences. The second part of the article gives a comparative analysis of the pathology of CB. Neoplasia of the CB in humans, namely, paraganglioma, in most cases, is part of a genetic MEN syndrome (multiple endocrine neoplasia). In dogs, paraganglioma is also involved with multiple neoplasia formations throughout the body, including endocrine and neuroendocrine glands. From this perspective, dogs are the most suitable specimens for studying carotid body tumors and their involvement in a MEN-like syndrome.